2019
DOI: 10.3389/fphar.2019.00250
|View full text |Cite
|
Sign up to set email alerts
|

A C-Terminal Fragment of Chlorotoxin Retains Bioactivity and Inhibits Cell Migration

Abstract: Chlorotoxin was originally isolated from the venom of the Israeli scorpion Leiurus quinquestriatus, and has potential as a tumor imaging agent based on its selective binding to tumor cells. Several targets have been suggested for chlorotoxin including voltage-gated chloride channels, and it has been shown to have anti-angiogenic activity and inhibit cell migration. The structure of chlorotoxin is stabilized by four disulfide bonds and contains β-sheet and helical structure. Interestingly, the reduced form has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, Othman et al showed that residues 29-36 (8 C-ter residues) of CTX directly interact with MMP-2 (Othman et al, 2017). Furthermore, a recent study indicated that eight C-terminal residues of CTX are fundamental for its bioactivity and inhibition of cell migration (Dastpeyman et al, 2019). Seven C-ter residues of CTX and MeICT are identical and only Y 29 in CTX has been replaced with F 29 in MeICT, that both are aromatic residues with similar biochemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Othman et al showed that residues 29-36 (8 C-ter residues) of CTX directly interact with MMP-2 (Othman et al, 2017). Furthermore, a recent study indicated that eight C-terminal residues of CTX are fundamental for its bioactivity and inhibition of cell migration (Dastpeyman et al, 2019). Seven C-ter residues of CTX and MeICT are identical and only Y 29 in CTX has been replaced with F 29 in MeICT, that both are aromatic residues with similar biochemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…The endocytosis of the complexes induced via binding of CTX contributes to chloride ion efflux in cells [114,115]. Synthetic chlorotoxin derivatives were used successfully in both preclinical and clinical trials of glioma therapies [116][117][118]. Potassium transporters play a crucial role in cell membrane potential.…”
Section: Anticancer Therapies Targeting Ion Channelsmentioning
confidence: 99%
“…It is being evaluated as a new diagnostic drug in a phase II/III clinical trial to determine how well the drug can help distinguish between tumor and normal tissue during surgery in pediatric primary central nervous system tumors (NCT03579602). What is unique with this peptide is that it is retained in the tumor and can cross the blood–brain barrier 96 . Chlorotoxin molecular targets include the CLC-3 voltage-gated chloride channel, annexin-2, and matrix metalloproteinase-2 96 99 .…”
Section: Setting Milestonesmentioning
confidence: 99%
“…What is unique with this peptide is that it is retained in the tumor and can cross the blood–brain barrier 96 . Chlorotoxin molecular targets include the CLC-3 voltage-gated chloride channel, annexin-2, and matrix metalloproteinase-2 96 99 . SOR-C13 is a carboxy-terminal truncation of soricidin, a 54-residue paralytic peptide found in the venom of the short-tailed shrew Blarina brevicauda .…”
Section: Setting Milestonesmentioning
confidence: 99%